Development of a diagnostic and management protocol for acute scrotum in a tertiary care hospital: A prospective observational study. - Mrigesh, Kumar; Suvit Jumde; Pradhan, Tanu (Student’s Journal of Health Research Africa, 2025)
Background: Acute scrotum is a urological emergency requiring timely evaluation to prevent testicular loss, particularly in cases of torsion. Differentiating torsion from inflammatory causes remains clinically challenging. This study aimed to develop and implement a structured diagnostic and management protocol for acute scrotum in a tertiary care setting. Methods: This prospective observational study was conducted at a tertiary care teaching hospital from August 2016 to October 2018. A total of 100 male patients presenting with acute scrotal pain, with or without swelling, were included. Clinical assessment, laboratory evaluation, and color Doppler ultrasonography were performed in all cases. Patients with findings suggestive of testicular torsion underwent emergency exploration, with orchidopexy performed for viable testes and orchidectomy for non-viable testes. Patients with inflammatory causes were managed conservatively. Follow-up was completed at 2 weeks and 1 month. Results: Of the 100 patients studied, testicular torsion (44%) and epididymo-orchitis (38%) were the most common etiologies, followed by acute hydrocele (7%), scrotal cellulitis/abscess (6%), and pyocele (3%). Color Doppler ultrasonography demonstrated high diagnostic reliability, particularly in differentiating torsion from inflammatory causes. Among the 44 torsion cases, 18 (41%) underwent orchidopexy and 26 (59%) underwent orchidectomy, with contralateral orchidopexy performed in all torsion patients. Conservatively managed patients showed significant clinical improvement, with 92% completing follow-up and reporting symptom resolution. Conclusion: The implementation of a structured clinical and diagnostic protocol enables timely diagnosis and appropriate management of acute scrotum, improving testicular salvage rates in torsion and ensuring effective conservative treatment in inflammatory conditions. Recommendation: Integration of standardized evaluation pathways and early referral protocols is strongly recommended to minimize diagnostic delays and prevent avoidable testicular loss.